Reconstructing black identity: The Black Panther, Frantz Fanon and Achilles Mbembe in conversation - Beyers, Jaco (HTS teologiese studies, 2019)
It is dehumanising to identify people in terms of colour. Stereotyping and discrimination come with racial identification. Black identity has been expressed in different forms over the centuries. For a long period black identity was a constructed identity assigned to black people through a white-dominated matrix. After the end of slavery, efforts were made to reconstruct black identity. This developed into two divergent lines: one resulting in an illusionary identity as identified by Frantz Fanon and a second line of thought of a continued search for a true authentic black identity as explicated by the Cameroon-born philosopher Achilles Mbembe. This process of creating a new authentic black identity is still ongoing and viewed by some as a pessimistic futile attempt. An example of the ongoing attempt for establishing an authentic black identity is illustrated by the movie Black Panther, which attempts to portray a different side of being black.